Screening for Adolescent Anxiety Disorders in a Pediatric Emergency Department - Ramsawh, Holly J. (2012)
OBJECTIVES: Adolescence is a time of increasing risk for some anxiety disorders. Scant data exist on adolescent anxiety in emergency department (ED) settings. We sought to characterize select clinical characteristics and healthcare utilization associated with anxiety disorders in a pediatric ED. METHODS: We screened a convenience sample of 100 adolescent-parent dyads presenting to the ED for the presence of child anxiety disorders using the 5-item Screen for Child Anxiety Related Emotional Disorders, parent (SCARED-P) and child (SCARED-C) versions. Additional demographic and clinical data were also collected. RESULTS: SCARED-P and SCARED-C screens identified probable anxiety disorder(s) in 26% to 33% of adolescent participants, respectively. Correlates of positive SCARED-C screens were female gender, asthma, presenting complaint involving headache or migraine, and school absenteeism due to physical problems. Correlates of positive SCARED-P screens were lower parental educational level, presenting complaint involving headache or migraine, and more medical specialty and total medical visits. Few anxious adolescents had received mental health services in the past six months. In multivariate models, female gender was independently associated with SCARED-C total score, and presenting complaint involving headache or migraine was independently associated with SCARED-P total score. CONCLUSIONS: The current pilot data suggest anxiety disorders are more prevalent among adolescent ED patients than in the general population, but largely untreated. Several demographic and clinical variables may help to identify occult anxiety disorders. Greater awareness of anxiety disorders in this population may assist in redirecting a pattern of low use of mental health services but higher overall healthcare utilization.